El presagio de un nuevo Madrid. El Ensanche Sur (1860-1878) - Vicente Albarrán, Fernando (Cuadernos de Historia Contemporánea, 2009)
Castro’s project about the urban extension of Madrid was approved, in 1860, to solve the serious problems of stacking and public health of the city. Thousand of immigrants came to the capital for improving their living status and most of them established their home and job in these new city areas. Besides the city planning, the south urban extension was transformed into an industrial area by the train, where low-class people lived. This paper analyzes the evolution of these new southern suburbs of Madrid through people who lived in them and the progressive social differences that were appearing among the different areas of the city.